1966
DOI: 10.1002/aja.1001180205
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of nerve endings in the nucleus of the trapezoid body and the ventral cochlear nucleus

Abstract: Large, calyciform axonal endings, as well as typical terminal boutons, have been previously described in the ventral cochlear nucleus and the nucleus of the trapezoid body by light microscopists. In the present study, these endings were examined with the electron microscope in chinchillas, rats, and a cat after perfusion fixation with osmium tetroxide. The calyces were found to consist of elongated processes arising from myelinated axons and making multiple synaptic contacts with perikarya and dendrites. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(103 citation statements)
references
References 19 publications
8
94
1
Order By: Relevance
“…Because the calycine endings are among the largest in the brain, they engender considerable interest. They are typified by multiple, punctate individual synaptic contacts, associated large, round synaptic vesicles (50-60 nm in diameter), coverings by astrocytic processes, and extracellular spaces between the ending and postsynaptic cell body [51,63,72,95,205]. Intra-axonal labeling and degeneration studies reveal that both large and small endings share these cytologic features, emphasizing the idea that synapses of primary auditory fibers are identical [28,51,203].…”
Section: Fine Structurementioning
confidence: 97%
“…Because the calycine endings are among the largest in the brain, they engender considerable interest. They are typified by multiple, punctate individual synaptic contacts, associated large, round synaptic vesicles (50-60 nm in diameter), coverings by astrocytic processes, and extracellular spaces between the ending and postsynaptic cell body [51,63,72,95,205]. Intra-axonal labeling and degeneration studies reveal that both large and small endings share these cytologic features, emphasizing the idea that synapses of primary auditory fibers are identical [28,51,203].…”
Section: Fine Structurementioning
confidence: 97%
“…Each input had all the electrophysiological characteristics ascribed to the calyceal inputs to these cells, suggesting that some cells may receive multiple calyces as described anatomically in the ventral cochlear nucleus (Lenn and Reese 1966). In the 101 cells we examined for the occurrence of this phenomenon (after the cell in which we first noticed it serendipitously), we identified it in six more cells; as discussed in the following text, this may represent an underestimate of the true frequency.…”
Section: Introductionmentioning
confidence: 92%
“…Axons from the globular bushy cells in the ventral cochlear nucleus (VCN) cross the midline in the trapezoid body and give rise to one or two calyces (Smith et al 1991). Anatomical studies in the young and mature rat (Casey and Feldman 1985;Kandler and Friauf 1993;Sätzler et al 2002;Taschenberger et al 2002), cat (Morest 1968a;Smith et al 1991), and other animals (e.g., Lenn and Reese 1966) have reported that each postsynaptic principal cell receives input from only one calyx. In addition to the calyceal synapse, other, smaller, bouton contacts onto the principal cell and its dendrites have been observed (e.g., Lenn and Reese 1966).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, globular bushy neurons of the anterior ventral cochlear nucleus (aVCN) and principal neurons in the medial nucleus of the trapezoid body (MNTB) are capable of firing action potentials that are faithfully locked to the phase of incoming stimuli at frequencies up to ϳ600 Hz (Brownell, 1975;Banks and Smith, 1992;Wu and Kelly, 1993;Taschenberger and von Gersdorff, 2000). MNTB neurons are important relay elements that receive a secure synaptic input from the contralateral aVCN via the calyx of Held (Lenn and Reese, 1966;Morest, 1968Morest, , 1973Forsythe and Barnes-Davies, 1993) and send an inhibitory projection to the ipsilateral medial superior olive (MSO) and lateral superior olive (LSO). Both the MSO and LSO also receive direct excitatory projections from the aVCN.…”
Section: Introductionmentioning
confidence: 99%